2021
DOI: 10.1101/2021.06.27.450087
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tracking and Measuring Local Protein Synthesis In Vivo

Abstract: Detecting when and how much a protein molecule is synthesized is important for understanding cell function, but current methods have poor cellular or temporal resolution or are destructive to cells. Here, we developed a technique to detect and quantify subcellular protein synthesis events in real time in vivo. This Protein Translation Reporting (PTR) technique uses a genetic tag that produces a stoichiometric ratio of a small peptide portion of a split fluorescent protein and the protein of interest during pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…We focused on the fact that Dendra2 has a substantially higher photoconversion property than other fluorescent proteins used for the existing split-pcFPs (Figure S2). A previous study has shown that Dendra2 can be divided between strands 10 and 11, enabling protein labeling by taking advantage of its spontaneous complementation . In this study, we develop a pair of nonfluorescent fragments of Dendra2 (split-Dendra2) that is reassembled and then recovers its photocontrollable fluorescence property only when the fragments are brought into proximity by PPIs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We focused on the fact that Dendra2 has a substantially higher photoconversion property than other fluorescent proteins used for the existing split-pcFPs (Figure S2). A previous study has shown that Dendra2 can be divided between strands 10 and 11, enabling protein labeling by taking advantage of its spontaneous complementation . In this study, we develop a pair of nonfluorescent fragments of Dendra2 (split-Dendra2) that is reassembled and then recovers its photocontrollable fluorescence property only when the fragments are brought into proximity by PPIs.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study has shown that Dendra2 can be divided between strands 10 and 11, enabling protein labeling by taking advantage of its spontaneous complementation. 8 In this study, we develop a pair of nonfluorescent fragments of Dendra2 (split-Dendra2) that is reassembled and then recovers its photocontrollable fluorescence property only when the fragments are brought into proximity by PPIs. To develop split-Dendra2 enabling PPI detection, we comprehensively investigated Dendra2 by dividing it into two fragments separately at their 14 different loop regions.…”
Section: ■ Introductionmentioning
confidence: 99%